1970
DOI: 10.1002/ps.2780010402
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mode of action of the acaricide fenazaflor

Abstract: The active ingredient of 'Lovozal' (fenazaflor) is hydrolysed in solution to 5,6-dichloro-2-trifluoromethylbenzimidazole (DTFB). Rat liver mitochondria were uncoupled by fenazaflor after a lag phase, while uncoupling by DTFB was immediate, and a similar situation occurred with mitochondria isolated from Tetranychus telarius L. (This is the first report of isolation of mite mitochondria.) Since both compounds ultimately have the same uncoupling activity, it is likely that fenazaflor exerts its effect only after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
8

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 6 publications
1
50
0
8
Order By: Relevance
“…The descriptor pro®le of class 3 chemicals (uncouplers of oxidative phosphorylation) is dominated by electronic charge parameters with major contributions of steric bulk. Most of them are hydrophobic weak acids that have protonophoric activities, i.e., they are able to transport H through the mitochondrial membranes [35,36]. For induction of uncoupling, an acid dissociable group, a bulky hydrophobic moiety and strongly electron withdrawing group(s) are required, such as derivatives of phenols, benzimidazoles, N-phenylanthranilates, salicylanilides, phenylhydrazones, salicylic acids, coumarins and aromatic amines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The descriptor pro®le of class 3 chemicals (uncouplers of oxidative phosphorylation) is dominated by electronic charge parameters with major contributions of steric bulk. Most of them are hydrophobic weak acids that have protonophoric activities, i.e., they are able to transport H through the mitochondrial membranes [35,36]. For induction of uncoupling, an acid dissociable group, a bulky hydrophobic moiety and strongly electron withdrawing group(s) are required, such as derivatives of phenols, benzimidazoles, N-phenylanthranilates, salicylanilides, phenylhydrazones, salicylic acids, coumarins and aromatic amines.…”
Section: Discussionmentioning
confidence: 99%
“…The principal patterns are alike, although the steric properties of class 4 compounds are more pronounced relative to log K OW and the values of electronic charge distribution descriptors are lower except DIPOL. Comparison of target sites reveals similar structural requirements for inhibitors of photosynthesis and uncouplers of oxidative phosphorylation [35,38,39]. The herbicide binding niche on the D-1 quinone-binding protein of photosystem II (PS II: a 32 Kdalton protein in thylakoid membranes) reveals two interaction sites ± histidine-215 and serine-264.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to explore the potential effect of other drugs. Dinitroaniline herbicides such as oryzalin, which was shown to cause disruption of plant cell microtubules (Corbett et al 1984), disrupt the microtubules of several protozoa including Tetrahymena (Stargell et al 1992) and protozoan parasites such as Trypanosoma spp. (Traub-Cseko et al 2001), Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether the four cyanobacterial strains could resist existing larvicides, some commercial chemical and biological larvicides were tested at the concentrations Table 1 Tolerance of cyanobacteria to temperature, salinity, and biological and chemical larvicides Chemspray respectively, are organophosphorous insecticides known to inhibit the acetylcholinesterase of susceptible mamalian cells (Corbett et al, 1984). Thiery et al (1991) reported that chemical larvicides did not affect the growth of some strains of cyanobacteria isolated from the French Mediterinean Coast.…”
Section: Resultsmentioning
confidence: 99%